MECHANISMS OF DEVELOPMENT OF CENTRAL AND PERIPHERAL NERVOUS SYSTEM DAMAGE IN HERPESVIRUS INFECTION - Ismailova Mexriban Olimbayevna; Nishanov Ergashali Joraxon o’g’li (Bright Mind Publishing, 2025)
Today, a serious increase in human viral diseases is observed all over the world, which makes pathological changes in the nervous system one of the common problems. Improving the effective treatment of patients with epilepsy due to post-viral encephalitis by diagnosing the clinical-neurological and neurophysiological features of this disease helps to improve the quality of life of patients and prevent disability, and indicates the urgency of this problem.
Keywords: Viral diseases, herpes infection, human herpes virus, рapillomavirus Infections.